Transgender identities and public policy in the United states: the relevance for public administration - Taylor, Jami Kathleen (2007)
This article examines an emerging issue within the field of governance, the intersection of public policy with transgender identity. It is important that administrators better understand this issue given the lack of consistency in the current policy framework. This article addresses transgender identity's intersection with employment law, marriage, hate crimes, and the current legal framework for sex reassignment in the United States. The article also addresses how transgender identity contrasts with gay and lesbian identities with regard to public policy. Given widespread bias against this population, administrators are called to ensure that these individuals receive equal and equitable policy treatment. - Reproduced.
Keywords: Public policy - United States; Public administration - United states; Public administration